(untitled) (International Journal of Environmental Sciences, 2025)
Background: Impaired bone quality significantly impacts dental implants’ prognosis because it alters implant stability, one of the most crucial requirements for successful implants. According to density, Carl E. Misch divided bone quality into four categories: D1, D2, D3, and D4. The strongest of all is Type D1, with 80% stronger trabeculae; Type D2 has a combination of porous and dense bone, with trabeculae that are 40%–60% stronger than Type D3; Type D4 has poor density and trabeculae that are 10 times weaker than Type D1. Purpose: The Present finite element analysis (FEA) assessed the influence of bone densities (D1, D2, D3, and D4) on the survival rate of implants by assessing the stress-strain distribution and displacement at the peri-implant area and on the implant system. Materials and Methods:A data library at the Qassim University Dental Clinic was searched for Cone Beam CT scans. The volume bone mineral density of cortical and cancellous bone related to its density (HU units) was established to get unique bone qualities. The cortical and cancellous volume percentages were estimated as per available literature and superimposed with the attained varying percentages to mimic altered bone qualities (D1, D2, D3, and D4). All 4 Groups were subjected to Finite Element Analysis using ANSYS (ANSYS14.5,USA). Meshes and modelling geometric shapes for the required components, boundary conditions were employed, and the outcomes were recorded and analysed for Von Mises Stress and deformation on the Implant system and peri-implant bone on all 4 models on a vertical load of 140N. Results: Maximum von Mises Overall stress was observed on D4 model (139.55MPa, soft bone), and less stress was noted on the D1, D2, and D3 Models. Maximum cortical bone stress (17.43 MPa) was noted on softer bone (D4), where minimum thickness cortical bone was available. Maximum Implant system stress was observed on the D4 model implant (74.79 MPa) due to poor quality bone as compared to the D1, D2, and D3 models (37.09 MPa, 54.21 MPa, and 45.27 MPa). Overall deformation/displacement was observed on soft bone D4 model (12.2 µm) as compared to harder bone D1, D2 & D3 models (5.6 µm, 5.5 µm, and 5.1 µm) respectively. Conclusions: The current study’s findings recommend that bone quantity and quality should be assessed before implant placement and loading are planned. Implant planning should be avoided in softer bone (D4) situations or done with the greatest restraint,especially in immediate implant placement. D2 or D3 bone quality is preferred for longer-lasting implants.